Transcending the Lamentations of Non-Identification Approaches to Teaching Students Ways To Write about 19th Century Black Literature - Grayson, Sandra M. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1996)
Most college students are not accustomed to writing about, reading, analyzing, or discussing 19th-century Black literature, especially slave narratives. As many educators try to include more Black literature in their curriculums, there is a growing need to develop successful methods to approach the texts so that students are prepared to write quality papers about Black literature. Some successful techniques for helping students move away from the "lamentations of non-identification" are: (1) remind students, by example, that they do not have to identify with the text to write about it; (2) use a structure moving students from background information about the text to an analysis of writing about the work; (3) incorporate multidimensional techniques to the study of the literature, such as using music; (4) use an interdisciplinary approach to texts; and (5) use a structure of modules for courses, moving students from one theme to another with continuity. (CR)
ERIC Note: Paper presented at the Annual Meeting of the Conference on College Composition and Communication (47th, Milwaukee, WI, March 27-30, 1996).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Black Literature; Higher Education; Literature Appreciation; Nineteenth Century Literature; Student Attitudes; Teaching Methods; Writing Assignments; Writing Instruction; Writing Strategies; Composition Literature Relationship; Slave Narratives; Opinion Papers; Reports, Descriptive; Speeches/Meeting Papers